2004
DOI: 10.1111/j.1366-9516.2004.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Place prioritization for biodiversity conservation using probabilistic surrogate distribution data

Abstract: We analyse optimal and heuristic place prioritization algorithms for biodiversity conservation area network design which can use probabilistic data on the distribution of surrogates for biodiversity. We show how an Expected Surrogate Set Covering Problem (ESSCP) and a Maximal Expected Surrogate Covering Problem (MESCP) can be linearized for computationally efficient solution. For the ESSCP, we study the performance of two optimization software packages (XPRESS and CPLEX) and five heuristic algorithms based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 33 publications
0
58
1
Order By: Relevance
“…Combination of niche-based distribution modeling and reserve selection algorithms is also a promising approach [67][68]. It works as an effective tool that should be applied in systematic conservation planning to identify and interconnect priority regions, particularly those already covered by natural protected areas [69].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Combination of niche-based distribution modeling and reserve selection algorithms is also a promising approach [67][68]. It works as an effective tool that should be applied in systematic conservation planning to identify and interconnect priority regions, particularly those already covered by natural protected areas [69].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…There is a long discussion about whether reserves selected using vegetation types represent species biodiversity data (Brooks et al 2004). For instance, in a review of articles on reserve selection in South America, Pinto & Grelle (2009b) found only one indexed article that uses vegetation types as target (Sarkar et al 2004), although there are other non-indexed reserve selection studies done in Brazil (e.g. Albernaz & Souza 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they focused on the design of robust heuristics. Similarly, Sarkar et al (2004) found little reason to prefer optimal to heuristic areaselection algorithms for their probabilistic data sets. For their large data sets, the optimal algorithms often required long computation times and produced no better results than the heuristic ones.…”
Section: Discussionmentioning
confidence: 99%